Human rights and state-corporate crimes in the practice of gas flaring in the Niger Delta, Nigeria - Izarali, M. Raymond (Critical criminology, 2016)
This article addresses the social harm of gas flaring by petroleum companies in the Niger Delta, Nigeria and makes a conceptual case for human rights and state-corporate crimes. It outlines the human and environmental harms caused, the role of the state and Shell and other corporate entities in producing such harms, the disregard shown to the communities when concerns are raised about the effects on their health and livelihood, and the disrepute brought to the administration of justice. It also outlines the insecurity spawned in the communities in the Niger Delta as a result of these harms and the high level of impoverishment suffered despite the wealth generated since the discovery of oil in the 1950s, thus broadly contributing to the literature on green criminology.